(3hUjI GdEeGe CHj MfjaI GdfYeGf dJdejPg jhSa Hf NGdO GdSeJj GdHUQj HGddZI GdaGQSjIs - (3GdJjej, Gdchaj, CHh MfjaI, GdfYeGf Hf KGHJ, J (B150 (3g`s ((3eOQSI GdSdWGf GdZGRj eMeO NGfs)
(3ChdgG (B:s
(3gPg hUjI GdEeGe GdCYXe QMeg Gddg dJdejPg jhSa NGdO GdSeJj GdHUQj EeGe CYXec TGcQ Ojs
(3BNQgG (B:s
(3RjQ GdMbjb Sf GcQjJe Th hUjJe Gjdg JeSc GjOhH Yed GjOGQjc QLhJ Gf JSde Ch eG Qe cg LejY CaGJOf SGde Chdg SjQI hJYjT SGdeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 36s
(3eYLe GdeDdajf(B: 4 /34s
(3cTa GdXfhf(B: 2 / 2015s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs